PEMANFAATAN LIMBAH KULIT SINGKONG DAN SEKAM PADI DALAM PEMBUATAN BIOBRIKET DENGAN PEREKAT TAPIOKA SEBAGAI BAHAN ALTERNATIF BIOMASSA - Ratu Intan Berlian; Lalu Ahmad Didik Meiliyadi; Bahtiar Bahtiar (Komunikasi Fisika Indonesia, 2023)
This study aims to determine the effect of sample comparison composition on moisture content, ash content, calorific value, mass density, combustion time and rate of combustion of biobriquettes. In this briquette, the samples tested are materials from processed waste products of cassava peel and rice husks with tapioca adhesive. This study uses six stages, namely the preparation stage, drying stage, mixing stage, combustion stage, and quality test stage. In testing the quality of briquettes, three samples were used in each briquetting test, namely samples A, B, and C, each of which was a ratio of cassava peel and rice husk of 10:90, 20:80, and 30:70. The results showed that the lowest water content was found in the ratio between cassava peel and rice husk 10:90, the lowest ash content was found in biobriquettes with a ratio of cassava peel and rice husk 10:90, the highest heating value was found in a ratio of 10:90, mass density the highest is in the ratio of 10:90, the fastest burning rate is in the ratio of 10:90, the longest burning time is in the ratio of cassava peel and rice husks of 10:90. So that the comparison composition of quality cassava peels and rice husks is if the addition of the composition of the rice husk samples is more in number than the composition of the cassava peels.